PENGARUH KUALITAS PELAYANAN DALAM MENINGKATKAN VOLUME PENJUALAN PT. PLN (PERSERO) AREA SIBOLGA - Rommel Sitohang; Henri Saragih (Universitas Methodist Indonesia, 2021)
Research objectives must be in line with the formulation of the problem, namely: to determine and analyze the effect of service quality in increasing the sales volume of PT. PLN (Persero) Sibolga Area. This research was conducted at PT. PLN (Persero) Sibolga Area on Jl. DR. FL. Lumban Tobing, Sibolga, North Sumatra, Indonesia. The research period starts from February 2021 to May 2021. The population of this study was all consumers who added 20,769 electric powers during the 2018-2020 period. Determination of the sample size in this study using the Slovin formula so that the number of samples becomes 100 people. The research instrument used a questionnaire and data analysis using multiple linear regression The results showed that the value of F count was 14.262 and the value of Sig. is 0.000. It is known that if the value of F count 18,150> F table 2,311 and the value of Sig is 0,000 <0.05, then Physical Evidence, Reliability, Responsiveness, Assurance, and Empathy together or simultaneously have a significant effect on Sales Volume. This is indicated by the coefficient of determination (Adjusted R-Square) being 0.401. Based on this value Physical Evidence, Reliability, Responsiveness, Assurance, and Empathy are able to influence Sales Volume by 40.1%, and the remaining 100% - 40.1 = 59.9% is explained by other variables or factors.